The influence of the synthesis route on the final properties of SnO2-based varistors - Parra, R.; Rodriguez-Paez, J. E.; Varela, José Arana [UNESP]; Castro, M. S. (Elsevier B.V., 2008)
A comparative study of two customary routes of ceramics processing applied to the synthesis of SnO2-based varistors is reported in this paper. Devices of equivalent composition were prepared through the Pechini method and through directly mixing the oxides without the addition of anti-agglomerants or binders. The microstructures of the sintered samples were characterised with X-ray diffraction and scanning and transmission electron microscopies. The electrical behaviour of the devices was studied on the basis of the current density versus electric field (J-E) characteristics and impedance spectroscopy measurements. The Pechini method ensures the homogeneity in the distribution of the additives in the tin oxide matrix but the formation of secondary phases seems to be independent of the synthesis route. Devices with similar non-linear coefficients of 18 and 21 were obtained through the mixed oxides route and the Pechini method, respectively. (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: powders : chemical preparation; tin oxide; varistors; Pechini